ASSESSMENT OF MEDICATION ADHERENCE AMONG PATIENTS WITH HYPERTENSION AND DIABETES MELLITUS IN URBAN FIELD PRACTICE - R, Manikandan; Sri Sai Sudha, Nandamuri; M, Logaraj (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The present study was conducted to assess the medication adherence among patients with hypertension (HTN) and diabetes mellitus in the urban area of Tamil Nadu and to assess the reasons for non-adherence. Methods: A cross-sectional study was conducted in an urban area of Tamil Nadu. A total of 100 subjects were enrolled in the study. The patients are diagnosed with HTN and diabetes was included in the study. Morisky medication adherence scale was used to measure adherence among the selected subjects and each patient's details were regarding non-adherence was noted. The results were tabulated. Results: In our study, the medication adherence of the patients was 84% and the non-adherence patients were 16%. Medication adherence was found to be more in male (58%) when compared with females (42%). In our study, the reasons for non-adherence include high drug cost was more when comparing other factors. In our study, the patients receiving drugs from the medical shop were more comparing with government and private hospitals. Conclusion: A four-fifth of the subjects is adherence to the prescribed medications. The patients having poor medication adherence due to the high cost of the drug and forgot to take use their medication.